Study of Residual Stress Relaxation Mechanics Using a Micro-indent Method - Diaz, Felipe Victor (2016)
The aim of this study is to show the feasibility and accuracy of a micro-indent method to comprehensively evaluate the relaxation mechanics of residual stress in specimens of rolled aluminium alloy. This micro-indent method was adapted to implement four annealing treatments. The residual displacements were measured using a high-accuracy measuring machine, which enables to decrease the absolute error down to ± 300 nm. This work presents an innovative data analysis using Mohr´s circles, which allowed to study all directions of the in-plane residual stress for different relaxation times. The results revealed that the relaxation process finishes when the residual stress relief is completed in some preferential directions, and then, a brief stress recovery phase begins.